An Uncommon Presentation of Spontaneous Rectus Sheath Hematoma with Acute Kidney Injury due to Obstructive Uropathy and Prerenal Azotemia. (13th July 2014) - Paschou, Eleni; Gavriilaki, Eleni; Kalaitzoglou, Asterios; Mourounoglou, Maria; Sabanis, Nikolaos
Abstract : Rectus Sheath Hematoma (RSH) represents an unusual entity which is characterized by acute abdominal pain and tender palpable abdominal mass usually, among elderly patients receiving anticoagulant therapy. We report the case of an 81-year-old woman admitted to our department due to acute abdominal pain and oligoanuria. The patient had recently been hospitalized due to acute myocardial infarction (AMI) and atrial fibrillation (AF) and received both anticoagulant and antiplatelet therapies. The radiological assessments revealed an extended Rectus Sheath Hematoma and bilateral hydronephrosis. Treatment of the hematoma required cessation of anticoagulants and antiplatelet agents, immobilization, blood and fresh frozen plasma transfusion, and administration of vasopressors. The patient recovered gradually and was discharged home fifteen (15) days later.